THE HOMONYMIC PROPERTIES OF PHRASEOLOGICAL UNITS IN UZBEK AND TURKISH LANGUAGES - S.B.Khursankulov; D.Z.Abduazimova (TADQIQOTLAR, 2026)
Abstract:This  article  presents  a  comparative  analysis  of  the  homonymic features  of  phraseological  units  in  the  Uzbek  and  Turkish  languages.  The  study identifies  the  semantic,  structural,  and  functional  characteristics  of  phraseological homonyms and highlights their patterns of use in speech. Within the scope of this brief research, phraseological units that are identical in form in both languages but differ in  meaning  are  examined  through  illustrative  examples.  The  findings  of  the  study contribute to a  deeper  understanding of Turkic phraseology and  are  of  significant importance for translation theory as well as for comparative approaches in linguistics.